Chemoselective imaging of mouse brain tissue via multiplex CARS microscopy - Pohling, Christoph; Buckup, Tiago; Pagenstecher, Axel; Motzkus, Marcus (Biomedical optics express, 2011)
The fast and reliable characterization of pathological tissue is a debated topic in the application of vibrational spectroscopy in medicine. In the present work we apply multiplex coherent anti-Stokes Raman scattering (MCARS) to the investigation of fresh mouse brain tissue. The combination of imaginary part extraction followed by principal component analysis led to color contrast between grey and white matter as well as layers of granule and Purkinje cells. Additional quantitative information was obtained by using a decomposition algorithm. The results perfectly agree with HE stained references slides prepared separately making multiplex CARS an ideal approach for chemoselective imaging.